2012
DOI: 10.1051/0004-6361/201117603
|View full text |Cite
|
Sign up to set email alerts
|

Doppler images of II Pegasi for 2004–2010

Abstract: Aims. We study the spot activity of II Peg during the years 2004-2010 to determine long-and short-term changes in the magnetic activity. In a previous study, we detected a persistent active longitude, as well as major changes in the spot configuration occurring on a timescale of shorter than a year. The main objective of this study is to determine whether the same phenomena persist in the star during these six years of spectroscopic monitoring. Methods. The observations were collected with the high-resolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 18 publications
7
41
1
Order By: Relevance
“…In some previous studies of II Peg (e.g. Berdyugina et al 1999), indications of flip flops were reported that the abrupt activity jumps from one longitude to another, separated roughly by 180 degrees, but the results of Lindborg et al (2011) and Hackman et al (2012) did not support this interpretation.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In some previous studies of II Peg (e.g. Berdyugina et al 1999), indications of flip flops were reported that the abrupt activity jumps from one longitude to another, separated roughly by 180 degrees, but the results of Lindborg et al (2011) and Hackman et al (2012) did not support this interpretation.…”
Section: Introductionmentioning
confidence: 85%
“…Berdyugina et al 1998aBerdyugina et al , 1999Gu et al 2003;Lindborg et al 2011;Hackman et al 2012) and magnetic field maps have been published (Kochukhov et al 2013;Carroll et al 2007Carroll et al , 2009). The star's photometric light curves have also been intensively studied with time-series analysis and spot-modeling methods (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies targeted II Peg with high-resolution spectroscopic observations with the goal to constrain the spot temperatures using TiO absorption bands (O'Neal et al 1998;Berdyugina et al 1998b) and to analyse configurations of the surface temperature inhomogeneities with the Doppler imaging technique (Berdyugina et al 1998a;Gu et al 2003;Lindborg et al 2011;Hackman et al 2012). Early DI images corresponding to the period between 1994 and 2002 suggested persistent presence of a pair of active longitudes and showed major changes in the surface structure on a time-scale of less than a year (Berdyugina et al 1998a(Berdyugina et al , 1999Lindborg et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Early DI images corresponding to the period between 1994 and 2002 suggested persistent presence of a pair of active longitudes and showed major changes in the surface structure on a time-scale of less than a year (Berdyugina et al 1998a(Berdyugina et al , 1999Lindborg et al 2011). More recent DI maps covering the years from 2004 to 2010 revealed the star entering a low-activity state characterised by a more random distribution of cool spots (Hackman et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation